Effects of inhaled stable xenon on cerebral blood flow velocity. - Giller, C A; Purdy, P; Lindstrom, W W (American Journal of Neuroradiology, 1990)
The effects of inhaled stable xenon gas on cerebral blood flow were studied with 23 transcranial Doppler examinations performed in 13 normal volunteers while breathing, 25, 30, or 35% xenon for 5 min. Doppler velocities from the middle cerebral artery rose significantly during inhalation in 85% of subjects and 78% of studies and decreased significantly in 15% of subjects and 17% of studies. These different velocity responses may represent different responses of pial vasculature to xenon. The mean velocity rise among those studies showing a significant increase was 38 +/- 3.6% (SEM). The velocity rise began 2 min after the start of xenon inhalation and increased rapidly, so that the velocities measured at the four times at which scans were obtained in our xenon CT protocol (0, 1.5, 3, and 5 min after the start of xenon inhalation) were significantly different. A consistent fall in the pulsatility of the Doppler waveform as the velocity increased provided evidence for xenon-induced vasodilation of the small-resistance vessels as the cause of the increase in flow velocity. Most subjects became mildly hyperventilated, so that the observed changes could not be attributed to hypercapnia. Inhalation of 25, 30, or 35% xenon for 5 min induces a delayed but significant rise in cerebral blood velocity. This suggests that cerebral blood flow itself may be rapidly changing during the process of xenon CT scanning. These changes may compromise the ability of the xenon CT technique to provide reliable quantitative measurements of cerebral blood flow.